Mosquito larvicidal activity of Hyptis capitata leaves ethanolic extract and fraction against Culex quinquefasciatus - Nelsiani To'bungan; Wibowo Nugroho Jati (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2022)
Larvicidal potential of Hyptis capitata grown in Indonesia has not been extensively studied. Its leaves are extracted with the maceration method using ethanol as the solvent. Furthermore, this study aims to use the ethanolic leaf extract of the H. capitata for larvicidal assays against instar III/IV larvae of Culex quinquefasciatus with different concentrations, including 1000, 500, 250, 125, and 62.5 µg/mL. Fractionation of the extract was carried out by vacuum liquid chromatography, and obtained four fractions, namely fractions F1, F2, F3, F4. Fractions were also used for the larvicidal assay. The constituents of the extract were then analyzed with the GC-MS method to predict the components involved in its toxicity. Larvicidal data obtained were analyzed using regression analysis to determine the LC50 value. Analysis of variance was carried out with one-way ANOVA using Tuckey HSD-test on the SPSS ver. 26 at 95% confidence and significance P<0.05. H. capitata ethanolic leaf extract has a higher level of toxicity than its fraction, with LC50 value 990.90 µg/mL. H. capitata ethanolic leaf extract are capable of providing a toxic effect on larvae, with a mortality percentage of up to 50% more. Some compounds that were assumed to play a role in its toxicity include pentadecanoic acid, 2,6,10,14-tetramethyl-, methyl ester; 1-heptadecyne; 9-tetradecen-1-ol, acetate; oxyrane, deodecyl-; 9,12,15-octadecatrienal; and 6,11-dimethyl-2,6,10-dodecatrien-1-ol. These finding indicate that the ethanolic leaf extract of H. capitata has the potential to be developed as a biolarvicidal agent against C. quinquefasciatus.